Development of Economic Based Generative Learning to Facilitate Students' Concept Understanding Ability - Fiska Wahyuni Siregar; Henny Indrawati; Neni Hermita (STAI Hubbulwathan Duri, 2024)
In the modern era of digitalization, teachers serve as a pivotal element in the educational process, instrumental in shaping future human resources. Students, particularly in the field of economics, are encountering increasingly competitive challenges, underscored by the rapid evolution of knowledge and technology. Independent learning emerges as a critical response to these challenges, aligning with the requisites of 21st-century education through the augmentation of technology-mediated learning environments. This study proposes the development of economic e-modules based on generative learning, aiming to furnish a valid and practical learning tool. The investigation enlisted a sample comprising 107 students and three educators across three schools. Employing the Research and Development (RD) ADDIE Model—comprising stages of Analysis, Design, Development, Implementation, and Evaluation—the study scrutinized the efficacy and validity of the proposed e-modules. The findings reveal that the e-modules exhibit high validity, with scores of 0.975 and 0.987 for the e-modules and their content, respectively. Practicality assessments conducted across School 1, School 2, and School 3 in Pekanbaru yielded percentages of 94.29%, 91.42%, and 100%, respectively, demonstrating the modules' applicability and utility in the context of economic instruction. Economic e-modules rooted in generative learning principles not only enhance the enjoyment of the learning process but also significantly improve students' conceptual understanding and active engagement. This research underscores the potential of such e-modules to revolutionize economics education, catering to the evolving demands of both students and the educational paradigm of the 21st century.